Pengaruh Kualitas Pelayanan terhadap Loyalitas Nasabah dengan Kepuasan Nasabah sebagai Variabel Mediasi - Sawitri, Ida Ayu Gede Intan; Kawiana, I Gede Putu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This study aims to determine the effect of service quality on customer loyalty with customer satisfaction as a mediating variable. This research was conducted at the Village Credit Institution (LPD) of the Kaba-Kaba Traditional Village in Tabanan with a research sample of 98 customers. The research method used is quantitative. Data collection techniques are observation, interviews, documentation, literature and questionnaires. The data analysis techniques used are Descriptive Analysis, Path Analysis and Sobel Test. The results showed that the quality of service has a positive and significant effect on customer loyalty. The quality of service has a positive and significant effect on customer satisfaction. Customer satisfaction has a positive and significant effect on customer loyalty. Service quality has an indirect effect on customer loyalty through customer satisfaction